(untitled) (Research, Society and Development, 2021)
This work consisted of the review and study of several articles, which helped to report the use of ozone therapy in each area of dentistry. In order to demonstrate the different means and pathologies treated by different professionals in the dental field, this review managed to expose in detail the powders and cons of the therapy, obtaining a result of great power in its use by studies. Concluding that it is one of the best alternatives for those who have access and that it needs a lot of research to demystify this option, showing skeptics that it is not a fairy tale but a real alternative.